Determinants of academic performance of students of agronomy and zootechnics courses at a private higher education institution (Research, Society and Development, 2021)
In this work, an analysis of the main results obtained in a research on the socioeconomic profile of students in the Agronomy and Zootechnics courses at FAZU - Faculdades Associadas de Uberaba was performed, in view of the performance in the Chemistry discipline that is taught in the first period of the courses. The investigative method was based on the application of a questionnaire to academics at the beginning of the academic semester. From the results, it was possible to identify that the courses are formed by a young audience, with an average age of 17 to 20 years old, predominantly male, single, mostly from Uberaba and with family income between 1 and 6 salaries minimums. The approval rate of these students in the discipline of Inorganic and Analytical Chemistry at FAZU was 58.46%. Half of the students who answered the questionnaire work regularly. The majority is made up of students from a public school, having just finished high school, considering previous learning, in chemistry, weak. They sleep an average of 8 hours a day, and study only days before the test. Taking into account students from day and night courses, most (60%) are from evening courses. From some data analyzed in the research, it is possible to notice that night students, even with some adversities such as higher average age, the majority coming from public schools and with lower family income, the average approval for the discipline of Inorganic Chemistry and FAZU's analytics is greater.